Non-closure of the Free Peritoneal Flap During Laparoscopic Hernia Repair of Lower Abdominal Marginal Hernia: A Retrospective Analysis - Xu, Qian; Zhang, Guangyong; Li, Linchuan; Xiang, Fengting; Qian, Linhui; Xu, Xiufang; Yan, Zhibo (Frontiers in Surgery, 2021)
Background: During lower abdominal marginal hernia repair, the peritoneal flap is routinely freed to facilitate mesh placement and closed to conclude the procedure. This procedure is generally called trans-abdominal partial extra-peritoneal (TAPE). However, the necessity of closing the free peritoneal flap is still controversial. This study aimed to investigate the safety and feasibility of leaving the free peritoneal flap in-situ. Methods: A retrospective review was conducted on 68 patients (16 male, 52 female) who underwent laparoscopic hernia repair between June 2014 to March 2021. Patients were diagnosed as the lower abdominal hernia and all required freeing the peritoneal flap during the operation. Patients were divided into 2 groups: one group was TAPE group with the closed free peritoneal flap, another group left the free peritoneal flap unclosed. Analyses were performed to compare both intraoperative parameters and postoperative complications. Results: There were no significant differences in demographic, comorbidity, hernia characteristics and ASA classification. The intra-operative bleeding volume, visceral injury, hospital stay, urinary retention, visual analog scale (VAS) score, dysuria, intestinal obstruction, surgical site infection, mesh infection, recurrence rate and hospital stay were similar among the two groups. Mean operative time of the flap closing procedure was higher than for patients with the free peritoneal flap left in-situ (p = 0.002). Comparisons of postoperative complications showed flap closure resulted in a higher incidence of seroma formation (p = 0.005). Conclusion: Providing a barrier-coated mesh is used during laparoscopic lower abdominal marginal hernia repair, it is safe to leave the free peritoneal flap in-situ and this approach may prevent the occurrence of seromas.